Brain potentials in the processing of complex sentences: an ERP study of control and raising constructions - Featherston, S; Gross, M; Münte, T F; Clahsen, H (Journal of psycholinguistic research, 2000)
In the present study we made use of Event-Related Potentials (ERPs) to examine raising and subject control constructions in German. Our most salient result is that the ERPs elicited at the empty subject position of a raising construction are clearly different from those elicited at the corresponding position of an otherwise identical subject control construction, the former producing a stronger P600. We argue that this result provides an electrophysiological correlate of the theoretical distinction between NP trace and PRO.